Urolithiasis in Pregnancy: A Review of Current Management Strategies - Łącki, Jakub; Skrzypek, Emilia; Czechowska, Małgorzata; Rogozińska, Alicja; Kasznicki, Michał; Beśka, Wiktor; Jackowiak, Karol; Micek, Natalia; Kalisiak, Michał; Kamela, Mikołaj (Quality in Sport, 2026)
Background. Urolithiasis during pregnancy is a complex clinical challenge occurring in approximately 8.3 per 10,000 pregnancies. Physiological changes increase stone risk, while standard diagnostic and therapeutic options (e.g., CT, ESWL) are restricted due to fetal safety concerns. Unmanaged symptomatic stones significantly elevate the risk of pyelonephritis, premature labor, and preeclampsia. Aim. To synthesize recent evidence and outline the current multidisciplinary consensus for managing pregnant patients with urolithiasis. Materials and methods. A review of 19 key studies, including large population-based cohorts, meta-analyses, and clinical surveys, focusing on imaging, conservative management, and endourological interventions. Results. Pregnant women frequently present with atypical symptoms. Ultrasound remains the gold-standard first-line imaging modality, with non-contrast MRI as the preferred second-line option. Approximately 95% of cases can be successfully managed conservatively. When intervention is required, both temporary drainage using a JJ stent and primary ureteroscopy (URS) demonstrate high obstetric safety (>99% normal pregnancy outcomes). However, URS provides definitive stone clearance with an approximately 1% complication rate, compared with a 45% rate of minor complications and rapid stent encrustation associated with temporary drainage. Conclusions. A multidisciplinary approach based on shared clinical judgement is essential. Conservative therapy is prioritized, however, primary URS by experienced teams is the preferred definitive treatment if intervention is required.